PEMBUATAN MEMBRAN DARI KOMPON KARET SINTETIS UNTUK KOMPONEN MESIN BURSTING TESTER PADA PENGUJIAN KUAT LETUP KULIT ATASAN SEPATU - Suharyanto (Politeknik ATK Yogyakarta, 2018)
Membrane is a thin layer which separates glycerine material from the material of the sample leather shoe tops to be tested in Bursting Tester machine. Membrane is elastic, if pressed will return to original shape. Membrane is also resistant to oil of glycerine. Membrane served as a filter in the samples to be tested, so the membrane is submerged in oil or glycerine. The purpose of the study is to make membrane product from Nitrile Butadiene Rubber (NBR) type synthetic rubber material because NBR is resistant to oil and is elastic. Membrane production used compounding and vulcanization method. Compounding is the process of mixing NBR with auxiliary chemicals such as Silica, Carbon black which served as filler. Added ZNO and Stearic acid as activators of BHT addition served as antioxidant, paraffin oil as softener, Mercapto Benzo Thiazole (MBT) Tetra Methyl Thiuram Disulfide (TMTD), Polypropylene Ether Glycol(PEG) 4000 as accelerator, Sulphur as vulcanizing agent. The formation process was making compound into product in accordance with the purpose of production. Vulcanization process was compound maturation by press moulding at 150oC and 125 kg/cm2 for 10 minutes. Membrane production results were tested for tensile strength, tearing strength and elongation in three treatments. The tensile strength values were 18,32 N/mm2; 9,69 N/mm2 and 12,07 N/mm2. The elongation values were 319 % , 347 % and 425 % with an average of 222 %. The tearing strength values were 1,96 N/mm2 , 1,87 N/mm2 and 2,02 N/mm2 with an average of 1,95 N/mm2